Educational paradigms: in pursuit of a new reference (Research, Society and Development, 2020)
Considering theoretical assumptions about educational paradigms, this study points to necessary changes in pedagogical concepts towards a theoretical-practical framework capable of nurturing moral and ethical values. It refers to a conception that aims at human development in its wholeness; that values the care of oneself, of the other and the environment; that allows critical and dialogical reflections; and that, through solidarity practices, seeks a new type of society by means of changing attitudes. The study focuses on the ecosystem paradigm, which boosts the enchantment towards education, without, however, disregarding the impacts and/or contributions of the other paradigms to education. As contributions, the paper introduces a profile of teachers who educate and a profile of students who are educated, within the scope of pedagogical trends that permeate educational paradigms.